The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2494/photopolymer.30.633
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between NIR and UV-Sensitized Radical and Cationic Reactivity of Iodonium Salts Comprising Anions with Different Coordination Behavior

Abstract: ) were tested regarding their efficiency as radical initiator to initiate radical polymerization according to a sensitized mechanism. A NIR LED emitting at 790 nm was applied to initiate sensitized polymerization applying the polymethine S2265 as sensitizer. Change of the sensitizer resulting in spectral overlap with emission of UV-LED emitting at 395 nm complimented the experiments to understand the behavior of these iodonium salts under different exposure conditions. Furthermore, formation of protons was qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 21 publications
1
17
0
6
Order By: Relevance
“…Even if the absorption coefficients were extremely low at 785 nm (170 L•mol −1 •cm −1 ) and 940 nm (100 L•mol −1 •cm −1 ), the possibility to initiate the FRP of methacrylates in the NIR region was brilliantly demonstrated. Indeed, photopolymerization at these wavelengths is dominated by cyanines [145][146][147][148][149][150] but these compounds are expensive so that alternatives are actively researched. While polymerizing a resin composed of a mixture of three monomers (33.3 wt% of (hydroxypropyl)methacrylate (HPMA), 33.3 wt% of 1,4-butanediol dimethacrylate (1,4-BDMA) and 33.3 wt% of a urethane dimethacrylate monomer (UDMA), final monomer conversions of 92% upon irradiation at 785 nm and 60% upon irradiation at 940 nm could be obtained with the four component system Cbz_35/(t-Bu)Ph 2 I + /4-dppba/BlocBuilder®MA (0.1 wt%/ 3 wt%/2 wt%/2 wt%) where 4-dppba and BlockBuilder®MA stand for 4-(diphenylphosphino)benzoic acid and the acronym for a commercial alkoxyamine respectively.…”
Section: Carbazole-based Bopidysmentioning
confidence: 99%
“…Even if the absorption coefficients were extremely low at 785 nm (170 L•mol −1 •cm −1 ) and 940 nm (100 L•mol −1 •cm −1 ), the possibility to initiate the FRP of methacrylates in the NIR region was brilliantly demonstrated. Indeed, photopolymerization at these wavelengths is dominated by cyanines [145][146][147][148][149][150] but these compounds are expensive so that alternatives are actively researched. While polymerizing a resin composed of a mixture of three monomers (33.3 wt% of (hydroxypropyl)methacrylate (HPMA), 33.3 wt% of 1,4-butanediol dimethacrylate (1,4-BDMA) and 33.3 wt% of a urethane dimethacrylate monomer (UDMA), final monomer conversions of 92% upon irradiation at 785 nm and 60% upon irradiation at 940 nm could be obtained with the four component system Cbz_35/(t-Bu)Ph 2 I + /4-dppba/BlocBuilder®MA (0.1 wt%/ 3 wt%/2 wt%/2 wt%) where 4-dppba and BlockBuilder®MA stand for 4-(diphenylphosphino)benzoic acid and the acronym for a commercial alkoxyamine respectively.…”
Section: Carbazole-based Bopidysmentioning
confidence: 99%
“…Im Allgemeinen stellte sich heraus, dass 2 d der beste Coinitiator für alle Systeme war, was durch den Vergleich der Polymerisationseffizienz zu Beginn und bei der endgültigen Umwandlung bestätigt wird. Es zeigt eine überraschend bessere Effektivität als das auf 2 b basierende System, das bisher als einer der effektivsten Iodonium‐Coinitiatoren angesehen wurde [44] . 1 d und 2 d funktionierten gut in Epoxiden ( M2 ), dem Vinylether M3 und dem Oxetan M4 a .…”
Section: Ergebnisse Und Diskussionunclassified
“…[20][21][22] Both Lalevée 16,23,24 and Strehmel [25][26][27] and their coworkers have elegantly shown visible-to-NIR photocuring of acrylates and epoxies using Type II photosystems. For example, recent reports have shown that NIR polymerization chemistry can be either rapid (< 60 s) when using a high intensity (≥ 400 mW/cm 2 ) laser diode at 785 nm, 23 or reactive under low intensity (~30 mW/cm 2 ) LED light centered at ~790 nm, yet requiring longer exposure times (> 100 s) 25 . This apparent tradeoff between reaction rate and incident light intensity necessitates a closer examination of visible-to-NIR photosystems to advance state-of-the-art photocuring.…”
Section: Xanthenes and Cyanines Have Received Considerable Attention mentioning
confidence: 99%